THE TEACHING SPEAKING BY USING DISCUSSION METHOD TO INCREASING ORAL PROFICIENCY IN THE REKAYASA PERANGKAT LUNAK (RPL) OF ELEVENTH CLASS AT SMKN I LABANG- BANGKALAN - Yuswantoro Yuswantoro (JURNAL ILMIAH BAHASA DAN SASTRA, 2017)
There are many classrooms activities that can be used by the teacher to get goal in teaching learning process, for example conversation, role-playing, discussion, debates, and games. All of them represent strategies for providing the imotional involvement necessary for authentic interaction in the classrooms. In the Rekayasa Perangkat Lunak(RPL) of Eleventh Class at SMKN I Labang- Bangkalan, one of method which has used the teacher that is discussion method. In this research, the researcher will discuss about the implementation of discussion method in that class and problems are faced of discussion method in that class. In this study, the researcher tried to uses the theory of Sanjaya (2009) says that discussion method is very effective in helping students interact in class, learn to solve problems, answer questions, and improve student’s skills in english speaking. Then, researcher uses qualitative research study as a way to analyze the problems in applying these methods in class discussion. Observations and interviews are a research tool that will be uses to assist the research process. Total population in the Rekayasa Perangkat Lunak(RPL) of Eleventh Class at SMKN I Labang- Bangkalan consist of eight classes. However, in this study the researcher take sample only one class that is From the result, writer finds that the application of discussion method which conducted in the classroom, there is one form of kinds discussion method which has effect to the others forms. That’s why in stating that the discussion method suitable in the uses of English teacher as a strategy in teaching and learning in the classroom. Key words: Discussion Methods, Oral Proficiency